Integrasi Maslahah Mursalah dan Metode SMART terhadap Efisiensi Anggaran Pemerintah untuk Mendukung Pertumbuhan Ekonomi UMKM - Muhammad Syauqy Ridha Rabby; Hasan Zaki Mubarak; Hanathul Murohami Ashari; Dea Puspita Anggraiani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyse the integration of the concept of Maslahah Mursalah in fiqh muamalah with the SMART (Specific, Measurable, Achievable, Relevant, Time-bound) planning method as an effort to improve the efficiency of the government budget allocated to the Micro, Small and Medium Enterprises (MSMEs) sector. MSMEs are the backbone of the national economy, but are often constrained by budget inefficiencies and weak real needs-based policies. A qualitative approach was used in this study, with literature study techniques and in-depth interviews with budget planning officials and MSME actors. The results show that the integration of maslahah values that consider the public good, when combined with the SMART method, can improve the effectiveness and accountability of public budget use. This concept can be used as a policy model based on Islamic ethics and modern management.